PSIKOEDUKASI BERBASIS KETAHANAN KELUARGA PADA IBU DALAM MENINGKATKAN KAPASITAS PENGASUHAN PADA ANAK PRASEKOLAH - ALIFAH INDALIKA MULYADI RAZAK (Jurnal Buah Hati, 2022)
The concept of family resilience is a family condition that has toughness, physical material and psycho-mental-spiritual abilities to live independently, develop themselves and their families to achieve a state of harmony in improving physical and spiritual well-being. Family resilience needs to be owned by every family so that every family member can fulfill their rights and obligations, which is marked by an attitude of serving as a sign of nobility, intimacy between husband and wife towards a good quality marriage, parents who educate their children, husband and wife who lead with love. , as well as children who hold and honor their parents. Its strategic goals and the concept of family resilience are supported by data from the Central Statistics Agency which shows there are around 81,210,230 families in Indonesia based on the Inter-Census Population Survey in 2015. The purpose of this research is to provide training to mothers to improve their caring capacity in preschool children who are tested through the dimensions of the instrument parenting capacities focus on stimulation. Program effectiveness was tested through the-before-after study design experimental research method, based on the dimensions of parenting capacity consisting of: (1) children's cognitive development and potential through interaction; (2) communication, speaking and responding to children's language and questions; (3) encourage and participate in children's play; (4) promote educational opportunities; and (5) facilitating children to face life's challenges. The training strategy was developed using family resilience-based psychoeducation which was packaged through blended training for mothers for 10 days involving 50 mothers in Cimahi City, West Java. The results show that the mother's ability to raise children effectively increases after participating in a family resilience-based psychoeducation program.AbstrakKonsep ketahanan keluarga merupakan kondisi keluarga yang memiliki ketangguhan, kemampuan fisik material dan psikis mental spiritual guna hidup mandiri, mengembangkan diri, dan keluarganya untuk mencapai keadaan harmonis dalam meningkatkan kesejahteraan lahir dan batin. Ketahanan keluarga perlu dimiliki oleh setiap keluarga agar setiap anggota keluarga dapat terpenuhi hak dan kewajibannya, yang ditandai dengan sikap melayani sebagai tanda kemuliaan, keakraban antara suami-istri menuju kualitas perkawinan yang baik, orangtua yang mendidik anaknya, suami-istri yang memimpin dengan penuh kasih, serta anak-anak yang menaati dan menghormati orangtuanya. Strategisnya tujuan dan konsep ketahanan keluarga didukung dengan data Badan Pusat Statistik yang menunjukkan terdapat sekitar 81.210.230 keluarga di Indonesia berdasarkan Survei Penduduk Antar Sensus di tahun 2015. Tujuan penelitian ini adalah memberikan pelatihan pada ibu meningkatkan kapasitas pengasuhannya pada anak prasekolah yang diujikan melalui instrument dimensions of parenting capacity focus pada stimulation. Efektivitas program diuji melalui metode penelitian eksperimen the-before-after study design, berdasarkan dimensi kapasitas pengasuhan yang terdiri atas : (1) child’s cognitive development and potentional through interaction; (2) communication, talking and responding to the child’s language and questions; (3) encouraging and joining the child’s play; (4) promoting educational opportunities; dan (5) facilitating child to meet challenges of life. Strategi pelatihan disusun menggunakan psikoedukasi berbasis ketahanan keluarga yang dikemas melalui blended training pada ibu selama 10 hari dengan melibatkan 50 orang ibu di Kota Cimahi, Jawa Barat. Hasilnya menunjukkan bahwa kemampuan ibu dalam mengasuh anak efektif meningkat setelah mengikuti program psikoedukasi berbasis ketahanan keluarga.